A PRESUPPOSITIONAL ANALYSIS OF SPECIFIC INDEFINITES WITH REFERENCE TO TRANSLATION FROM ENGLISH INTO ARABIC - Misbah. M.D. AL-Sulaimaan; Ayed. H. Omar (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Presupposition is a process which enables people to communicate through which the addressee uses semantic and pragmatic elements to understand the message. For the addresser, presuppositional analysis is to be done before delivering a speech; for the addressee before answering and for the translator before translating. Specificity is about specific individuality or thing in the mind of the addresser and this individual or thing is to be reached by the quantificational or referential method by the addressee. In both English and Arabic, the less indefinite the more specific and the more indefinite the less specific. This study seeks to achieve the following aims: (1) specifying and studying different patterns of specific indefinites in books and periodicals of semantics, semiotics and pragmatics, (2) discovering any matches between English and Arabic regarding indefinites in general and specificity in particular, (3) choosing presuppositional analysis as a model for translating the specified patterns of specific indefinites and then justifying them, and (4) pinpointing the similarities and differences between specific indefinites and definites. To achieve the above mentioned aims, the current thesis hypothesises that: (1) in most cases indefinite articles do not determine specificity, but presuppositional analysis does, (2) the addressee may achieve specificity by means of presuppositional analysis, some adjectives, quantifiers as well as co-text and context, (3) the addressee faces problems for presupposing specific and non specific indefinites with the source language and the case will be more problematic for the translator, (4) specific indefinites may be known or un-known for the addresser, and the addressee depends only on context in presuppositional analysis, and (5) it is easier for the addressee, through presuppositional analysis, to reach specificity when the addresser reports and acts and not only reports. To test the validity of the aforementioned hypotheses, the following procedure is used: (1) six texts, of twelve well-known scholars, have been selected from books of semantics and pragmatics, (2) these texts have been rendered and analysed with respect to presuppositional analysis by ten M.A students in the Department of Translation / College of Arts / University of Mosul / 2012-2013, and (3) an eclectic model has been derived from Russell’s (1905) and Fodor and Sag’s (1982) for presuppositional analysis of specific indefinites. The main findings have verified the hypotheses and finally the study ends with some recommendations for pedagogical implications and some suggestions for further studies